Concept Of Aharvidhi According To Ayurveda - Kushwaha, Somesh; Ojha, Aruna (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda is a holistic health care system of medicine originated in ancient Vedic civilization of India, which is more than 5000 years old. To attain healthy life Ayurveda concentrates on various rules & regulations. Like – Dincharya, Ritucharya. Aahar vidhi is one of important factor among them. How to eat, what to eat and what not to eat, where to eat, all rules are very well described in in Ayurveda. Ahara is the most important factor in our life. Health as well as disease depends on Aahar As growth, strength, happiness, good health, intelligence, complexion and the alertness of senses are traceable to food and its inequality causes illness. The treatment principle in Ayurveda is mainly based on preventive aspect first rather than curative. Healthy life starts with healthy food. Aahar plays vital role in healthy and diseased condition. The strength and complexion of person will enhance only if he practices healthy diet regimen. Many concepts related to Aahar vidhi are said in our Ayurveda texts like, Ashta Aahar vidhividhan, Dwadashashan pravicharna, Shadras concept, Panchmahabhut concept, Aahar bhed (types of food), Aacharya charaka told eight rules to take food which he called Ashta ahar vidhi vidhan. As per Ayurvedic classics “Deho hi Aahar sambhavah.”